The Competitiveness and Export Performance of Indonesian Coffee in The Organization of Islamic Cooperation (OIC) - Zuhdi, Fadhlan; Asshagab, Sri Milawati; Rambe, Khoiru Rizqy; Destiarni, Resti Prastika (Integrated Journal of Business and Economics (IJBE), 2024)
Since its establishment in 1969, the Organization of Islamic Cooperation (OIC) has served as a platform for Islamic countries worldwide to cooperate in various sectors, including economic, social, and cultural. One longstanding form of economic cooperation among OIC countries is in the field of trade. Indonesia, as one of the major producers and exporters of coffee, has engaged in coffee trade with OIC countries, and this cooperation has continued to the present day. This research aims to assess the competitiveness and export performance of Indonesian coffee to OIC using the Revealed Comparative Advantage (RCA) and Constant Market Share (CMS) methods. The results show that Indonesian coffee exports to OIC are competitive but have a declining growth rate. Meanwhile, the export performance of Indonesian coffee to OIC demonstrates good performance in following market distribution trends but shows shortcomings in meeting market preferences. Therefore, enhancing internal trade cooperation within OIC, partnering strategies with competing countries, and measures such as improving technology accessibility and evaluating responsive export policies are necessary.